A recessive mutation, immune deficiency (imd), defines two distinct control pathways in the Drosophila host defense. - Lemaitre, B (1995)
In this paper we report a recessive mutation, immune deficiency (imd), that impairs the inducibility of all genes encoding antibacterial peptides during the immune response of Drosophila. When challenged with bacteria, flies carrying this mutation show a lower survival rate than wild-type flies. We also report that, in contrast to the antibacterial peptides, the antifungal peptide drosomycin remains inducible in a homozygous imd mutant background. These results point to the existence of two different pathways leading to the expression of two types of target genes, encoding either the antibacterial peptides or the antifungal peptide drosomycin.